Dampak Perkembangan Teknologi Digital Terhadap Hukum Lembaga Pembiayaan (Jurnal Sosial Humaniora dan Pendidikan, 2025)
The rapid development of digital technology has brought significant transformations in various sectors, including the financial institution industry. Innovations such as fintech, artificial intelligence, and blockhain have changed convetional business models and created new challenges for the existing legal framework. This study aims to analyze the impect of digital technology developments on the law of financial institutions in Indonesia, especially in the context of consumer protection, cyber risk mitigation, and regulatory adjustments. The research method used is normative juridical with a literature study approach, reviewing various laws and regulations legal theories, and related literature. The results of the study indicate that current financial institution law needs to adapt proactively to accommodate the dynamics caused by digital technology.